Land, Gender, and Food Security - Doss, C; Summerfield, G; Tsikata, D (Routeledge, 2014)
Since 2008, a surge in large-scale land acquisitions, or land grabs, has been taking place in low- and middle-income countries around the globe. This contribution examines the gendered effects of and responses to these deals, drawing on nine studies, which include conceptual framing essays that bring in debates about human rights, studies that draw on previous waves of land acquisitions globally, and case studies that examine the gendered dimensions of land dispossession and loss of common property. Three key insights emerge: the evolving gender and land tenure literature provides valuable information for understanding the likely effects of land deals; some of the land deal issues transcend gender-equity concerns and relate to broader problems of dispossession and loss of livelihoods; and huge gaps remain in our knowledge of gender and land rights that require urgent attention and systematic integration of gender analysis into mainstream research
Keywords: Gender; land rights; land acquisitions; food security; land grabs; O13